Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
Trần Phương Linh

\(y\)\(-\)\(\dfrac{2}{7}\)\(=\)\(\dfrac{8}{9}\)

Kirito-Kun
10 tháng 9 2021 lúc 15:23

\(y-\dfrac{2}{7}=\dfrac{8}{9}\)

<=> \(y=\dfrac{8}{9}+\dfrac{2}{7}\)

<=> \(y=\dfrac{74}{63}\)

Dương Bảo Huy
10 tháng 9 2021 lúc 15:24

Y=74/63

Dương Ngọc Nguyễn
10 tháng 9 2021 lúc 15:24

undefined

Lấp La Lấp Lánh
10 tháng 9 2021 lúc 15:24

\(y-\dfrac{2}{7}=\dfrac{8}{9}\Rightarrow y=\dfrac{8}{9}+\dfrac{2}{7}\)

\(\Rightarrow y=\dfrac{56+18}{63}=\dfrac{74}{63}\)

༺ミ𝒮σɱєσиє...彡༻
10 tháng 9 2021 lúc 15:25

\(y-\dfrac{2}{7}=\dfrac{8}{9}\)

\(y=\dfrac{8}{9}+\dfrac{2}{7}\)

\(y=\dfrac{56}{63}+\dfrac{18}{63}\)

\(y=\dfrac{74}{63}\)

Kiều Hồng Mai
10 tháng 9 2021 lúc 15:32

Đáp án : \(\dfrac{74}{63}\)

Nam Sơn Bùi
10 tháng 9 2021 lúc 15:34

y-2/7=8/9

y=8/9+2/7

y=74/63

Ngọc Anh
10 tháng 9 2021 lúc 16:35

=74/63

Thượng Nguyễn
10 tháng 9 2021 lúc 21:15

y=74/63